Land easements: Development and problems of safeguarding the rights - G.A. Volkov (Ученые записки Казанского университета: Серия Гуманитарные науки, 2019)
The formation and development of land easements in modern Russia, differences from the history of their development in other countries have been studied. The establishment of public easement as a legal institution has been considered. The similarity of “private” and public land easements and its causes have been analyzed. Special attention has been paid to the problem of safeguarding the land rights in connection with the establishment of land easements for placement (construction) and reconstruction of various types of objects. The specifics of land easement formation in Russia and other countries, associated primarily with the development of private property rights, have been discussed. It has been shown that the system restrictions imposed in Russia on the right of private ownership of land, including other rights to land, in the public interest began to develop as a result of the need to ensure them due to the privatization of enterprises, buildings, and structures with comprehensive state ownership of land and other natural resources. The goal was not only and not so much associated with the development of private ownership of land, but with the need to ensure the state and local governance in the use and protection of land. The legal institution “public easement” originated in the Soviet law as a restriction of the rights to use land in the public interest, for example, for prospecting, exploration, hunting, etc.